PENGARUH KOMPETENSI MENGAJAR GURU DAN FASILITAS BELAJAR TERHADAP HASIL BELAJAR SISWA DI SMA NEGERI 7 BINTAN DESA NUMBING KECAMATAN BINTAN PESISIR KABUPATEN BINTAN - Astriyani Astriyani; Gimin Gimin; Hendripides Hendripides (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to determine the effect of teaching competence of teachers and learning facilities to the results for students at SMAN 7 Bintan Bintan village numbing Coastal District of Bintan regency. This research was conducted at SMAN 7 Bintan from May 2015 through June 2015. The method used is descriptive quantitative method. A population of 53 students and 47 students sampled. Data collection instrument used was a questionnaire using a Likert scale for the independent variables: teaching competencies of teachers (X1) and learning facilities (X2). The data analysis technique used is multiple linear regression. The result showed that the teaching competence of teachers and learning facilities simultaneously affect the students' learning outcomes. This is based on the results of analyzes, calculations show F count> F table (10.313> 3.195). While partially teaching competence of teachers and learning facilities affect the learning outcomes of students of class X and XI IPS SMAN 7 Bintan. This is evidenced by the t test, teachers' teaching competence variables obtained t 2,790 with a value ttabel1.679 and learning facilities obtained t 2,059 with a value ttabel1.679. So it can be concluded that the teaching competence of teachers and learning facilities effect on student learning outcomes with a contribution of 31.9% and the remaining 68.1% is influenced by other factors not examined as school environmental factors, community factors, physical factors, and psychological factors.Keywords: influence, competence level of teaching teachers, facilities, learning outcomes